Knowing the word components of the classical languages as a precursor to understanding the old words and their anchoring in the language system - Králová, Eliška (Bohemistyka, 2023)
The paper considers the role of word-forming components from classical languages – especially prefixes and prefixoids – in the system of national languages. What effect does advancing globalization and internationalization have on the vocabulary? In addition to a linguistic view of the issue, the paper aims to map the didactic approaches dealing with components from classical languages. Globally, their knowledge is considered one of the useful tools to improve literacy and second language acquisition. With advancing globalization and the need to communicate at international level not only in scientific terminology, the question remains how Latin and Greek morphemes are or should be integrated into language teaching at different levels of the education system and how to enhance pupils’ use of knowledge in vocabulary development and comprehension of academic and other texts in mother tongue and foreign language.